Soil fungal community and co-occurrence network patterns at different successional stages of black locust coppice stands - Tian, Huimei; Li, Liangzhe; Zhu, Yunpeng; Wang, Chengcheng; Wu, Mengxue; Shen, Weixing; Li, Chuanrong; Li, Kun (Frontiers in Microbiology, 2025)
Background and aimsBlack locust (Robinia pseudoacacia L.) plantations transition from seedling to multi-generation coppice systems, leading to declines in productivity and biodiversity. However, the structural and functional reorganization of soil fungal communities during this transition remains poorly understood. This study aimed to characterize fungal community dynamics across successional stages of black locust stands and assess their implications for soil health and ecosystem resilience.MethodsSoil fungal communities in three black locust stands (first-generation seedling forest, first- and second-generation coppice forests) were analyzed over one year using ITS high-throughput sequencing. We evaluated fungal diversity, guild composition, and co-occurrence networks, integrating statistical analyses (PERMANOVA, ANOSIM, FUNGuild) and network theory to assess seasonal and successional shifts.ResultsFungal richness and diversity remained stable across stand types and seasons. However, these factors dramatically altered the soil fungal community structure. Shifts in fungal community composition were observed from seedling to coppice stands: Ascomycota dominance decreased (72.9 to 57.9%), while Basidiomycota increased (6.5 to 11.6%). Significant changes in the relative abundance of certain fungal guilds were observed by both stand conversion and seasonal variation (p < 0.05). However, the overall fungal guilds composition was only significantly affected by the seasonal variation, rather than stand conversion (p > 0.05). Furthermore, saprotrophic fungi dominated in autumn/winter (66.49–76.01%), whereas symbiotic fungi peaked in spring (up to 7.27%). As forests transition from seeding to coppice stands, the percentage of negative edges, average degree, and relative modularity of the fungal community co-occurrence networks all gradually decreased. Those suggested that the conversion of black locust stands decreased the connectivity between fungal species, formed less organized structure, increased homogeneity of function among microbial communities, reduced ecological functionality, and decreased resistance to environmental changes. Seasonal temperature fluctuations further modulated network complexity, with summer samples showing heightened edge density but reduced cooperation.ConclusionOur findings suggest that the conversion of forests can significantly shift the soil fungal community structure and assembly, favoring Basidiomycota over Ascomycota and reducing network stability. These shifts signal progressive soil nutrient depletion and functional homogenization, potentially compromising ecosystem resilience. Seasonal guild dynamics highlight fungi’s role in nutrient cycling, with saprotrophs driving litter decomposition in colder months. This understanding suggest that forest management practices must prioritise the preservation of early successional stages. This is vital to support diverse fungal communities and complex community networks and ensure the stability, functionality and resistance of fungal communities. Restoration efforts must focus on promoting fungal resilience through targeted soil amendments and habitat diversification to enhance ecosystem stability and functionality.